TELAAH LITERATUR SISTEMATIS TENTANG IMPLEMENTASI ASESMEN AUTENTIK DAN BERBASIS KOMPETENSI - Rahmi Nur Salamah; Yusi; Dodo Murtado; Rosynanda Nur Fauziah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Twenty-first century education demands assessment systems that evaluate not only cognitive performance but also learners’ ability to apply knowledge, skills, and attitudes in real contexts. Authentic and competency-based assessments offer strategic approaches to achieving comprehensive evaluation. This study aims to analyze their concepts, principles, and implementation in improving learning quality. A systematic literature review of 30 scholarly articles, research reports, and educational policies published within the last decade was conducted. The findings reveal that authentic assessment effectively fosters critical, creative, collaborative, and communicative skills through contextual and real-world tasks. Competency-based assessment, meanwhile, emphasizes the integrated measurement of cognitive, affective, and psychomotor competencies. The integration of both approaches produces a valid, holistic, and relevant assessment model aligned with 21st-century educational and workplace demands. Nonetheless, implementation challenges persist, including limited teacher understanding, the need for continuous professional development, and the creation of objective scoring rubrics. The study recommends strengthening educators’ capacity to design authentic, competency-based assessments and encouraging institutional policy support for effective and sustainable implementation.